Energy transfer and localization in optochemotronic emitter with electrodes modified using the Langmuir-Blodgett technique - Zholudov, Yu.T.; Rozhitskii, N.N. (Functional Materials, 2005)
Problems of the excitation energy transfer and localization under biradical recombination reaction have been considered for an optochemotronic emitter containing the working electrode with a layer of electrochemiluminophore molecules deposited thereon using the Langmuir-Blodgett technique. A couple of reagents including 9,10-diphenyl anthracene and p-terphenyl has been proposed for efficient transformation of electric energy into light at electrochemical reaction in the system mentioned.